Análise do conversor DAB utilizando modulação triple phase shift com algoritmo de otimização e circuito de auxílio à comutação - Costa, Pablo Fernando Soardi (2022)
With the growth of the use of renewable sources for the generation of electric energy, the systems of distribution and transmission of energy have been going through significant changes. As the photovoltaic and wind renewable generation sources are currently more prominent, the systems must become more robust with regard to the intermittence of these sources. For this reason, the insertion of energy storage systems (Energy Storage Systems - ESS) to assist in the stability of the system has been widespread nowadays. However, for energy storage systems to be used, there is a need to interface with the rest of the system. For this to become possible, power electronics have a fundamental role through static power converters. In these applications, the Dual Active Bridge (DAB) converter has gained a lot of attention from researchers. Thus, this Thesis presents the analysis of the DAB converter when subjected to Phase-Shift Modulation (PSM) and Triple Phase Shift (TPS) modulations. TPS modulation adds new degrees of freedom in DAB converter operation compared to PSM modulation by introducing the duty cycle on the primary Full-Bridge (D1) and secondary Full-Bridge (D2) in addition to the phase-shift angle ( ) between transformer primary and secondary voltages. Thus, the behavior of the converter can be evaluated for the entire power range for different operating points with TPS. Making use of TPS, the most efficient choice of operating points can be defined, taking into account the apparent circulating power of the converter, which can provide a reduction in commutation and conduction losses. In order to achieve higher efficiencies, determining an optimized control trio (D1, D2 and ) for each operating point becomes necessary. For this, a search algorithm is proposed that uses as a figure of merit the relationship between the active output power and the total apparent power of the converter, called Power Factor (PF). In addition, several switching aid circuits (CAC) are analyzed, since the DAB converter operates without soft switching for low loads, in addition to having low efficiency at these operating points. As a result, switching aid circuitry is used to extend the soft-switching range of the DAB converter. Thus, a proposal for a topological variation of the DAB converter is presented with the insertion of a CAC, which will operate at the low output load points of the converter and where the gain d of the converter is greater than one (d > 1). The behavior of the DAB converter with the TPS modulation determined by the proposed algorithm and with the proposed CAC are validated through a prototype with a nominal power of 500 W.